THE IMPACT OF AI CHATGPT APPLICATION ON ENGLISH STUDENT’S ACADEMIC WRITING PRODUCTIVITY AND QUALITY - Sa'diyah, Siti Halimatus; Zainuddin, Zainuddin; Hamdani, Beny (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to assess the impact of using ChatGPT on the productivity and quality of students' writing. This study used a mixed-methods qualitative and quantitative method involving 10 English study program students from three universities. Data were collected through writing assignments and questionnaires, and analyzed using descriptive statistical tests, paired sample T-tests, and Pearson Correlation. The results showed a significant increase in the number of words written and the efficiency of time spent on assignments after using ChatGPT. In addition, the use of ChatGPT was also associated with an increase in the quality of writing, especially in grammar and fluency. This study concluded that ChatGPT was effective in increasing the productivity, efficiency, and quality of students' writing, although it is necessary to be aware of the potential for dependency that can reduce the development of students' critical thinking skills.